Fragments of mind: a thesis on the subject of experience, the structure of consciousness, and split-brain patients - Lövgren, OSJK (2023)
Neuropsychological research on so-called split-brain patients—individuals whose corpus callosum has been severed as a treatment for severe epilepsy—has revealed the possibility of startling breakdowns in the transmission of sensory information between the cerebral hemispheres. These experimental results have often been interpreted as demonstrating that split-brain patients have two streams of consciousness. In opposition to such views, this thesis argues for a conception of split-brain patients as having a single stream of consciousness that’s disunified in highly specific experimental settings but unified outside of those settings. It is also argued that conceptions of split-brain patients as having two unified streams of consciousness and conceptions according to which they have one consistently unified stream of consciousness rely on a mistaken assumption: That a set of experiences belong to a stream of consciousness if and only if all the contemporaneous experiences in the stream are unified with each other.